Food waste management in Shanghai full-service restaurants: A senior managers' perspective. (10th June 2020) - Filimonau, Viachaslau; Zhang, Huining; Wang, Ling-en
Abstract: The challenge of food waste in the foodservice sector of China is under-examined. This paper advances knowledge by exploring the food waste management practices adopted in a sample of Shanghai full-service restaurants. Through 22 in-depth semi-structured interviews with senior managers it establishes the significance of the food waste challenge and identifies Chinese food consumption habits as a major cause. Despite the pronounced role of consumers in food waste generation, restaurateurs largely fail to engage them in mitigation. To mitigate food waste occurring on customer plates, changes to the Chinese dining culture should be facilitated via nation-wide campaigns aiming to raise public awareness of food waste when eating out. The government of China should lead on the design of such campaigns, ideally involving celebrities for better consumer appeal and academics for the assessment of their effectiveness. The national government should also provide free-to-attend specialist training to restaurant managers and staff on how to mitigate food waste occurring in kitchens. Highlights: Explores food waste management in a sample of full-service restaurants in Shanghai. Establishes the significant magnitude of food waste generation. Pinpoints the Chinese dining culture as a major cause. Highlights the mostly passive nature of existing mitigation approaches. Elaborates on the interventions required for more effective mitigation.